Non-Market Leadership Experience and Labor Market Success: Evidence from Military Rank - LEE, Myoung-Jae (Institutional Knowledge at Singapore Management University, 2005)
There has been much recent interest in the effects of pre and non-market skills on future labor market outcomes. This paper examines one such effect: the effect on future wages of military leadership experience among Vietnam generation American men. We study rank, not just veteran status. We argue that rank is a good measure of pre-market leadership skills because of the clear military hierarchy and the primarily youth experience of Vietnam service. Two sources of selection bias are accounted for: non-random military entry and eventual rank attained. We apply a modified 2-stage parametric sample selection method. The rank premia on future wages are estimated using the parametric selection corrections and a propensity score matching with two indices. We find evidence of a leadership premium, but not a veterans’ premium. It is the rank that matters. If one joins the military believing that military service commands a future wage premium, he had better become an NCO or an officer.